Twenty-year systematic review of the hip pathology, risk factors, treatment, and clinical outcomes in artistic athletes - dancers, figure skaters, and gymnasts - Bolia, I.; Utsunomiya, H.; Locks, R.; Briggs, K.; Philippon, M. J. (Clinical Journal of Sport Medicine, 2018)
Objective: To identify (1) the predominant level of evidence of the clinical studies regarding the hip pathology, risk factors, treatment, and clinical outcomes in artistic athletes (dancers, figure skaters, and gymnasts) (2) the most commonly reported hip pathology, risk factors, treatments, and clinical outcomes in dancers, figure skaters, and gymnasts. Methods: To conduct this systematic review PubMed, EMBASE, and Scopus databases were searched for relevant studies and pertinent data were collected from the eligible articles. Included were studies which reported hip injuries in artistic athletes, the risk factors, treatment, and/or the clinical outcomes. We excluded case reports or irrelevant studies. No meta-analysis was performed because of study heterogeneity. The methodical index for nonrandomized studies (MINORS) criteria were used for quality control. Main Results: Thirty-eight studies were included in the analysis. The mean MINORS score was 13.6 ± 4.6 points indicating fair quality of evidence of the included articles. The predominant level of evidence was level IV. Chondrolabral pathology and muscle injuries were the most commonly reported pathologies. We found only 2 risk factor analysis studies; however, many studies reported risk correlation between artistic sports or imaging findings and hip pathology. Treatment strategies were reported in only 7 studies, clinical outcomes are significantly underreported. Conclusion: Chondrolabral pathology was the most commonly reported hip pathology in artistic athletes, however, prospective cohort studies are necessary to really understand these injuries and their associated risk factors. The lack of clinical outcomes is significant and future data collection is required to assess the effectiveness of the various treatments.